2008
DOI: 10.1073/pnas.0801097105
|View full text |Cite
|
Sign up to set email alerts
|

Design of protein function leaps by directed domain interface evolution

Abstract: Most natural proteins performing sophisticated tasks contain multiple domains where an active site is located at the domain interface. Comparative structural analyses suggest that major leaps in protein function occur through gene recombination events that connect two or more protein domains to generate a new active site, frequently occurring at the newly created domain interface. However, such functional leaps by combination of unrelated domains have not been directly demonstrated. Here we show that highly sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 44 publications
2
107
0
Order By: Relevance
“…Here, protein design may aim at the creation of novel domain interfaces possibly with enzymatic function or adaptation of interfaces of oligomerization or repeating unit assembly that are perturbed when steric restraints are not properly taken care of in the design. [56][57][58][59][60][61][62] Immunoglobulin domains and Fv fragments are versatile modules of proven value in biotherapeutics engineering. 1 Our CODV design differs from all previously reported designs because we do not N-or C-terminally attach VL and VH domains to create linearly extended domain strings as in, for example, diabody (Db), single-chain variable fragment (scFv), or DVD-Ig formats.…”
Section: Discussionmentioning
confidence: 99%
“…Here, protein design may aim at the creation of novel domain interfaces possibly with enzymatic function or adaptation of interfaces of oligomerization or repeating unit assembly that are perturbed when steric restraints are not properly taken care of in the design. [56][57][58][59][60][61][62] Immunoglobulin domains and Fv fragments are versatile modules of proven value in biotherapeutics engineering. 1 Our CODV design differs from all previously reported designs because we do not N-or C-terminally attach VL and VH domains to create linearly extended domain strings as in, for example, diabody (Db), single-chain variable fragment (scFv), or DVD-Ig formats.…”
Section: Discussionmentioning
confidence: 99%
“…Peptide-based ligands RGSIDTWV (B1) and PQPSDTWV (B2) bind the affinity clamp with K d values of 0.6 and 5 nM, respectively, by inducing association of the PDZ and FN3 domains and structuring of the connecting linker (27,28). To create a peptide-responsive version of TVMV, we replaced the protease-cleavable linker in the AI-TVMV module with the ePDZb1 version of the affinity clamp (27). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we sought to incorporate a receptor scaffold that undergoes a large conformational transition on ligand binding between the TVMV's catalytic and AI domains. As a model receptor, we chose an "affinity clamp"-an artificial two-domain receptor composed of a circularly permutated Erbin PDZ domain connected by a flexible serine-glycine linker to an engineered fibronectin type III (FN3) domain (27,28). Peptide-based ligands RGSIDTWV (B1) and PQPSDTWV (B2) bind the affinity clamp with K d values of 0.6 and 5 nM, respectively, by inducing association of the PDZ and FN3 domains and structuring of the connecting linker (27,28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, creation of multi-domain proteins is not just to bring together individual domains because dramatic changes may occur at their newly formed interfaces. Huang et al found that the optimization of the interface between PDZ and FN3 domains by combinatorial library selection of FN3 loops using phage display could create new binding interface that contributes to a dramatic increase of binding affinity and specificity (Huang et al, 2008).…”
Section: Synthetic Proteinsmentioning
confidence: 99%